Costs and benefits of congestion in two-sided markets: Evidence from the dating market - Tobias Lehmann; Camille Terrier; Rafael Lalive (Queen Mary University of London, School of Economics and Finance, 2023)
Congestion is a widespread phenomenon in two-sided markets, but evidence on its costs and benefits is limited. Using data from an online dating platform, we document a large excess demand, or congestion, for some women. By exploiting exogenous variation in the number of men and women using the platform, we show that congestion slows down matching time for men. Congestion benefits women who screen men's profiles quickly, by increasing their choice set. This asymmetry implies that policies aimed at reducing congestion can harm the side of the market that benefits from congestion.
Keywords: D4; D47; D62; D83; 330; Congestion; two-sided markets; online platforms